Top Hits 2007: Lagu Indonesia Populer - - (MEDIA PRESSINDO, 2007)
Kumpulan Lagu-lagu: Bunga Citra Lestari; Ada Band; Kahitna; Nidji; Kangen Band; Naff; Letto; Ari Lasso; Samson; Radja; Acha; Gigi; Ratu; ST 12; Ungu; Acha feat Irwansyah; Saint Loco feat Astrid; Pinkan Mambo; Agnes Monica; Tahta; Kerispatih; Ecoutez; Dewa; Rama; Melly Goeslaw; Erick; Astrid; Anima.